Politik Hukum Hak Masyarakat Adat Dalam Upaya Perlindungan Hak Ulayat. - Cyrilus Bomas Bolok Werang; I. Nyoman Nurjaya; Rachmi Sulistyarini (CV. AFDIFAL MAJU BERKAH, 2025)
Land is essential for communities throughout the world, including indigenous peoples in Indonesia. However, throughout Indonesian history, indigenous peoples have continuously strived to secure their rights and strengthen their position in governance and land ownership in Indonesia. Unfortunately, these efforts have not yielded results. In fact, customary rights continue to be violated in the name of development or 'national interests'. In fact, the position of indigenous peoples in obtaining their land rights is protected by the constitution as stipulated in the 1945 Constitution and Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA). Therefore, this study aims to determine the legal status of Indigenous Peoples in obtaining protection of Customary Land Rights based on positive law draft legislation in Indonesia. This research was conducted using a normative juridical research method with a legislative approach that will examine and analyze the application of rules or norms in various laws and regulations that will become new legal products, as well as various other literature as sources that can help in answering all existing problems.